2018
DOI: 10.1007/978-3-030-04612-5_21
|View full text |Cite
|
Sign up to set email alerts
|

Stable Marriage with Groups of Similar Agents

Abstract: Many important stable matching problems are known to be NP-hard, even when strong restrictions are placed on the input. In this paper we seek to identify structural properties of instances of stable matching problems which will allow us to design efficient algorithms using elementary techniques. We focus on the setting in which all agents involved in some matching problem can be partitioned into k different types, where the type of an agent determines his or her preferences, and agents have preferences over ty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…First, to better understand the NPcompleteness result, one may study the parameterized complexity with respect to the "degree" of incompleteness of the input preferences, such as the number of ties or the number of agents that are in the same equivalence class of the tie-relation. We refer to some recent papers on the parameterized complexity of preference-based stable matching problems [1,11,12,[14][15][16]29,[40][41][42]45] for this line of research. Second, we were not able to settle the computational complexity for complete preferences that are also single-peaked and single-crossing.…”
Section: Resultsmentioning
confidence: 99%
“…First, to better understand the NPcompleteness result, one may study the parameterized complexity with respect to the "degree" of incompleteness of the input preferences, such as the number of ties or the number of agents that are in the same equivalence class of the tie-relation. We refer to some recent papers on the parameterized complexity of preference-based stable matching problems [1,11,12,[14][15][16]29,[40][41][42]45] for this line of research. Second, we were not able to settle the computational complexity for complete preferences that are also single-peaked and single-crossing.…”
Section: Resultsmentioning
confidence: 99%
“…They observed that it is NP-hard even if the maximum length of a tie is constant but showed that Max-SRTI is fixed-parameter tractable when parameterized by the combined parameter "number of ties and maximum length of a tie". Meeks and Rastegari [30] considered a setting where the agents are partitioned into different types having the same preferences. They show that the problem is FPT in the number of types.…”
Section: Introductionmentioning
confidence: 99%